TANGGUNG JAWAB NOTARIS TERHADAP AKTA OTENTIK YANG BERAKIBAT BATAL DEMI HUKUM PADA SAAT BERAKHIR MASA JABATANNYA - Pertiwi, Selly Masdalia; Sirtha, I Nyoman; Dharsana, I Made Pria (Acta Comitas : Jurnal Hukum Kenotariatan, 2017)
Article 65 of the Law Number 2 of 2014 on the Amendment of Law Number 30 Year 2004 concerning the Notary Position states that: "Notary, Substitute Notary, Substitute Special Notary and the Acting Notary are responsible for every deed he or she has made??, although the Notary Protocol have been delivered to the depositary Notary Protocol". The ambiguity of norm in this Article leads to the interpretation that a Notary is responsible indefinitely for the rest of his/her life to the deed made, even though his/her tenure has expired. Notary is responsible for the deed he or she has made, without any exception when the deed is null and void. The question arises are as follows: what causes the authentic deed that is drawn up before Notary becomes null and void, and what is the liabilities of the Notary to the authentic deeds that declared to be null and void at the expiry time of his/her tenure. The study is a normative legal research, which departs from the obscurity of norms on the liabilities of a notary to authentic deeds considered to be null and void of the expiry of the notary’s tenure. The types of approach used were statutory and conceptual approaches. The legal materials used were primary, secondary, and tertiary legal materials, through the technique of literary review by a card system. To analyze the legal materials, it was used a descriptive and interpretative techniques as well as the grammatical interpretation. The results of this study indicated that an authentic deed of Notary considered to be null and void, if it does not meet the requirements of Article 1320 of the Civil Code regarding the terms of a valid agreement, Article 1868 of the Civil Code regarding the authenticity of the deed, Articles in the Law of Notary Position/UUJN particularly Article 16 paragraph (1) letter l, Article 16 paragraph (1) letter (k), Article 44, Article 48, Article 49, Article 50 and Article 51. In addition, a deed also must not conflict with the Notary Code of Ethics and the applicable laws and regulations associated with the deed. A notary who has ended his/her tenure is held responsible if the authentic act has been proved to be null and void and has not expired before the thirty years since the deed was made. Based on the theory of fautes personalles, notary is personally responsible for his/her actions. There are 4 (four) types of the Notary liabilities, namely: rise to civil liability, criminal liability, liabilities based on the UUJN and under the Code of Ethics of Notary.